2021
DOI: 10.1177/0361198121990681
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Vehicle Trajectory Estimation Based on Lane Change Detection using Smartphone Sensors

Abstract: As technology is moving rapidly toward automation and connectivity, it is of paramount importance to predict vehicle trajectories ahead of time. This not only enhances safety but also ensures mobility in a connected and automated environment. Previous studies have shown that, given the previous trajectory, the future trajectory can be estimated. But this method suffers from considerable drawbacks in the case of intersections as it cannot predict turning movements. It also requires advanced sensors that are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…It is observed that the trained model classifies 94% of the training samples with significantly high precision. Compared to studies [2], [16], [17], [18], proposed work outperforms classification of different driving behaviors, in terms of accuracy or data requirements. Figure 3 reflects higher recall for each of the classes in different cross validation folds.…”
Section: B Model Performancementioning
confidence: 85%
See 2 more Smart Citations
“…It is observed that the trained model classifies 94% of the training samples with significantly high precision. Compared to studies [2], [16], [17], [18], proposed work outperforms classification of different driving behaviors, in terms of accuracy or data requirements. Figure 3 reflects higher recall for each of the classes in different cross validation folds.…”
Section: B Model Performancementioning
confidence: 85%
“…The study [2] detects lane change with accuracy as low as 58% and high as 97% with various classification algorithms. It must be noted that this study uses Magnetometer, Accelerometer, and Gyroscope sensors besides GPS for data collection.…”
Section: B Model Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Other road geometries can also be used to test the synthesized traffic monitors under different conditions. Such monitors could also be extended to study more complex traffic interactions such as lane changes ( 40 , 41 ). Finally, online monitoring is the natural next step for the synthesis of real-time monitors.…”
Section: Discussionmentioning
confidence: 99%
“…Various smartphone sensors were used by previous studies ( 4 , 9 , 1820 ), including GPS, accelerometer, and gyroscope. This paper selects accelerometer and gyroscope because of their popularity and the consideration of battery consumption.…”
Section: Research Approachmentioning
confidence: 99%